"Building a Person": Legal and Clinical Personhood for Autistic and Trans Children in Ontario. Issue 2 (August 2020) - Pyne, Jake
Abstract: In the 1960s and 1970s, psychologists at the University of California, Los Angeles, operated two behaviour modification programs: one aiming to eliminate "feminine" behaviours in male-bodied children ("conversion therapy"), and one targeting autistic children's so-called problem behaviours (applied behavioural analysis or ABA). The head of the autism program referred to his work as "building a person." Decades later in Ontario, a radically incommensurate legal context sees conversion therapy banned while ABA receives millions of funding dollars. Drawing on legislation, case law, media, and clinical literature, I argue that the process of trans communities wresting themselves out from under conversion therapy involved discursively shifting from having a condition to being human—a process of "building a person"—still incomplete for autistic communities. While legal reforms protect some trans youth from harmful therapies, this does not extend to autistic trans youth, leading us to question at whose expense a rights-bearing trans person was built.